SAT0191 Platelets Induce Thymic Stromal Lymphopoietin Production by Endothelial Cells: Contribution To Human Systemic Sclerosis Fibrosis. (15th July 2016) - Truchetet, M.-E.; Demoures, B.; Guimaraes, J.; Bertrand, A.; Laurent, P.; Douchet, I.; Duffau, P.; Lazaro, E.; Richez, C.; Seneschal, J.; Constans, J.; Pellegrin, J.-L.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a complex systemic autoimmune disease characterized by microvascular dysfunction, immune activation and fibrosis affecting the skin and internal organs (1). Improved characterization of the fibrotic mechanisms involved in SSc is a keystone to developing biomarkers and effective disease-modifying therapies. The activation of endothelial cells (ECs) appears very early in the course of the disease, suggesting that chronic fibroblast activation may be at least partly the result of endothelial dysfunction (1, 2). However, the ability of the platelet/EC interaction to induce the secretion of factors directly involved in fibroblast activation and subsequent fibrosis in SSc remains uncertain. Objectives: The objective was to provide evidence of a new pathogenic loop implicating activated platelets, microvascular ECs and ECM production in SSc. Methods: A total of 203 SSc patients and 30 healthy donors (HDs) were prospectively enrolled between March 2012 and January 2015 at the University Hospital of Bordeaux. Immunohistochemistry and immunofluorescence analysis were performed on skin biopsy specimens from 18 SSc patients and 5 HDs. Serum TSLP levels were measured (ELISA) in the entire cohort. Human dermal microvascular ECs and fibroblasts were purified from normal and SSc patients skin biopsies. Extracellular matrix production by cultured fibroblasts was assessed by RT-qPCR. Results: Serum TSLP levels were significantly increased in SSc patients compared to HDs (p=0.0005) and were associated with a higher frequency of vascular damage (p=0.02). The proportion of dermal TSLP-positive cells was increased in the skin biopsies of SSc patients compared to HDs (p=0.0008) and was correlated with skin fibrosis (modified Rodnan skin score) (R=0.059, p=0.01). In SSc dermis, TSLP was mainly expressed by CD31-positive ECs. In vitro, activated platelets induced TSLP production by dermal microvascular ECs in an IL1β-dependent manner. Recombinant TSLP in normal fibroblasts reproducibly induced a pro-fibrotic profile as indicated by a significant increase in the collagen/collagenase ratio (p=0.03). Interestingly, this property was shared by fibroblasts purified from non-fibrotic TSLP-negative SSc skin, but lost with fibroblasts purified from TSLP-positive fibrotic skin. Conclusions: Taken together, these results identify dermal microvascular ECs as new contributors to TSLP production in SSc and suggest a potential mechanism by which platelets may profoundly affect the fibrotic process in SSc. References: Gabrielli A, et al., N Engl J Med 2009. Pattanaik D, et al., Front Immunol 2015. Disclosure of Interest: None declared